Long non-coding RNA TTN-AS1 regulates the proliferation, invasion and migration of triple-negative breast cancer by targeting miR-211-5p - Sun, Erhu (Mol Med Rep, 2021)
Increasing evidence has demonstrated that long non-coding RNAs (lncRNAs) serve important roles in numerous malignancies, including triple-negative breast cancer (TNBC). The lncRNA titin-antisense RNA1 (TTN-AS1) has previously been reported to promote tumorigenesis in various types of cancer. The present study aimed to investigate the potential role of TTN-AS1 in breast cancer and the associated underlying mechanisms. Following prediction by Starbase and confirmation by dual-luciferase reporter assay, TINCR was demonstrated to be a target gene for microRNA (miR)-211-5p. The expression levels of TTN-AS1 and miR-211-5p, which was predicted to be targeted by TTN-AS1, in TNBC tissues and in the breast cancer cell lines MDA-MB-453 and MDA-MB-231 were measured using reverse transcription-quantitative PCR. Following TTN-AS1-knockdown, cell proliferation was measured using a Cell Counting Kit-8 assay and colony formation assay, whereas cell invasion and migration were measured using Transwell and wound healing assays, respectively. Luciferase reporter assay was performed to verify the potential interaction between TTN-AS1 and miR-211-5p. In addition, rescue assays were conducted to investigate the effects of TTN-AS1 and miR-211-5p on TNBC development. The results demonstrated that TTN-AS1 expression was significantly upregulated, whereas that of miR-211-5p was found to be downregulated in TNBC tissues and cell lines compared with the matched adjacent normal tissues and normal breast epithelial cell line MCF-10A, respectively. Furthermore, TTN-AS1-knockdown inhibited the proliferation and invasive and migratory abilities of MDA-MB-453 and MDA-MB-231 cells, which was reversed following co-transfection with the miR-211-5p inhibitor. The results from luciferase reporter assay confirmed that miR-211-5p was a direct target of TTN-AS1, suggesting that TTN-AS1 may bind directly to miR-211-5p to negatively regulate its expression. In conclusion, the findings from the present study demonstrated that TTN-AS1 regulated the proliferation and invasive and migratory abilities of TNBC by targeting miR-211-5p. This study may provide some insights into the regulatory mechanism of TNBC and help the development of novel therapeutic interventions for TNBC.